**YYK**: "Mrs Kan, why is 0! = 1? Shouldn't it be zero?"**Mrs Pauline Kan**: "Well, it's just by definition!"So here's how you can actually show that 0! = 1; first of all, the '!' function is pronounced as

*factorial*, and not just an exclaimation mark. So what does this function do? Well, easy, if you have a positive integer

**, then**

*n***simply means to do the following:**

*n!*

*n! = n(n-1)(n-2)(n-3)...3(2)(1)*Well, so this means that

**is equal to the product of all positive integers preceding**

*n!***. But you see, there's another way to define**

*n***, and notice that:**

*n!*

*n! = n(n-1)!*And then you must agree that:

*1! = 1(0!)*But we all know that

**, and therefore we must agree that**

*1! = 1***. :)**

*0! = 1*
## No comments:

Post a Comment